Total Colonic Hirschsprung's Disease: The Hypermotility and Skin Rash Protocol - Vilanova-Sanchez, Alejandra; Ivanov, Monica; Halleran, Devin R.; Wagner, Andrea; Reck-Burneo, Carlos Albert; Ruth, Brenda; FIsher, Meghan; Ahmad, Hira; Weaver, Laura; Nash, Onnalisa; Buker, Danielle; Rentea, Rebecca Maria; Hoover, Erin; Maloof, Tassiana; Wood, Richard J.; Levitt, Marc A. (European Journal of Pediatric Surgery, 2020)
Introduction Total colonic Hirschsprung's disease (TCHD) presents a postoperative challenge due to multiple stools and perineal rash. We propose a protocol developed by pediatric surgeons and ostomy nurses to help prevent and treat hypermotility and severe perineal rash, especially in younger children who are not toilet trained.Materials and Methods We retrospectively reviewed our TCHD patients' charts from 2014 to 2017. All patients received a prescribed protocol for the treatment of hypermotility and perineal rash. We describe patients who underwent their pull through before and after the age of urine toilet training, and assessed the number of bowel movements, the perineal skin status, and growth.Results We treated 25 patients. Out of 25, 9 patients received a straight ileoanal pull through before the age of 18 months. Nine of 25 patients presented for a second opinion and had redo pull through. The remaining seven presented for bowel management after having a pull through at another institution. All these were treated following the hypermotility protocol. In total, 19 of 25 patients were not toilet trained. The mean number of bowel movements in all groups was 4 (3–5). All had a resolution of perineal rash and liquid stools after 3 months. Eleven of the 25 patients presented with failure to thrive. Two older patients experienced severe proctalgia requiring replacement of the ileostomy.Conclusion TCHD patients who underwent definitive pull through had nine high incidence of multiple stool, perineal rash, and low growth. With the implementation of bowel management care to slow the stools and a perineal skin protocol to treat the skin, we believe that these symptoms can be minimized even in patients who are not toilet trained. Since the implementation of this protocol, we have changed our practice to perform the pull through in such patients between the age of 6 and 18 months.
Keywords: total colonic Hirschsprung's disease; hypermotility; perineal rash; medical management